Stress analysis at bone-implant interface of single- and two-implant-retained mandibular overdenture using three-dimensional finite element analysis - Krishnakumar Lahoti; Anup Pathrabe; Jaykumar Gade (Wolters Kluwer Medknow Publications, 2016)
Purpose: The purpose of this research was to compare stress distribution on the bone between single implant-retained and two-implant-retained mandibular overdentures using three-dimensional (3D) finite element analysis. Materials and Methods: Two 3D finite element models were designed. The first model included single implant-supported mandibular overdenture placed in the midline of the mandible while the second model included two-implant-supported mandibular overdenture placed in the intra-foramen region, retained by ball attachment of the same diameter. The bone was modeled on the D2 bone depending on the classification given by Misch. A computed tomography scan of the mandible was used to model the bone by plotting the key points on the graph and generating the identical key points on the ANSYS Software (ANSYS, Inc., USA). The implant was modeled using appropriate dimensions as provided by the manufacturer. Stresses were calculated based on the von Mises criteria. Results: Stresses produced in the hard bone (HB) and soft bone (SB) were higher in single implant-retained mandibular overdenture while stresses produced around the denture as well as implant were higher in two-implant-retained mandibular overdenture. Conclusion: Within the limitations of the study, it had been seen that stresses produced were the highest on HB and SB in single implant-retained mandibular overdenture while stresses produced across the denture as well as implant were the highest in two-implant-retained mandibular overdenture.